Geoeconomic risk and digital assets: Evaluating bitcoin’s hedge role against Indonesia’s stock market - Darrel Afrian Tjahjadi; Rahmat Aryo Baskoro (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: This study assesses whether Bitcoin functions as a hedge and safe-haven against the Jakarta Composite Index/Indeks Harga Saham Gabungan (IHSG), particularly following the launch of the Spot Bitcoin ETF on January 10, 2024. Despite being widely portrayed as “digital gold,” prior studies show mixed evidence on Bitcoin’s protective role, especially in emerging markets. Given the relatively high volatility of the Indonesian stock market, evaluating Bitcoin’s risk-mitigation potential becomes increasingly relevant. Methods: The analysis employs the Dynamic Conditional Correlation GARCH (DCC-GARCH) model to estimate time-varying correlations between Bitcoin and IHSG, alongside Ordinary Least Squares (OLS) and quantile regression to examine hedge and safe-haven behavior under normal and extreme market conditions. The study explicitly compares pre- and post-ETF periods to capture potential structural changes. Findings: results indicate that Bitcoin does not function as a hedge, reflected in its positive and volatile average correlation with IHSG. Quantile regression further shows that Bitcoin fails to provide protection at extreme IHSG quantiles, both before and after the ETF launch. DCC-GARCH estimates confirm that correlations are time-varying but remain predominantly positive, failing to meet safe-haven characteristics. Moreover, the Spot Bitcoin ETF launch did not significantly enhance Bitcoin’s protective role, despite improving legitimacy and institutional participation. Conclusion: Overall, Bitcoin is better positioned as a diversifier with unstable correlation patterns rather than as a hedge or safe-haven for the Indonesian stock market, with important implications for investors, portfolio managers, and regulators. Novelty/Originality of this article: This study provides early emerging-market evidence on Bitcoin’s hedge and safe-haven properties using a combined DCC-GARCH, OLS, and quantile regression framework while explicitly comparing pre- and post-Spot Bitcoin ETF periods.